Prevalence and Correlation of Knowledge Level with Stress of Patients with Hypertension - Fidya Anisa Firdaus; Wina Widianti; Windi Oktavia; Suhanda (Inspirasi Foundation, 2020)
Introduction: High blood pressure causes several complications such as heart failure, kidney failure, stroke, circulation problems and death. Hypertension can be triggered by stress due to activation of the sympathetic nervous system which causes an intermittent increase in blood pressure. Patient's knowledge of hypertension is an important factor in controlling blood pressure and reducing stress levels. Objective: This study aims to determine the prevalence and correlation of the level of knowledge and stress in people with hypertension. Methods: This type of research is quantitative analytic with a cross sectional approach. The population in this study were hypertension patients in the Public Health Centre of Cijeungjing working area who were more than 30 years old with a total 101. The research sample was taken as many as 50 respondents with purposive sampling technique. The research instrument used was a questionnaire to measure the level of knowledge of hypertension and the perceived stress scale (PSS-10) as a measure of stress levels. Data were analyzed using SPSS version 20 with Chi Square statistical test. Results: The results showed that the majority of respondents had more knowledge than the average of 27 people (54%). While the majority of respondents' stress levels were in the medium category, namely as many as 33 people (66%). Conclusion: Based on the results of the analysis, it is concluded that there is no significant relationship between knowledge and stress levels of hypertensive patients as evidenced by the value α <ρ value (0.05> 0.067) and the value of chi square (X2) count <chi square (X2) table (5.709 < 12,592).